CERTAIN ASPECTS OF BID RIGGING IN BOSNIA AND HERZEGOVINA (EU and comparative law issues and challenges series (ECLIC), 2024)
The public procurement system aims to model the efficient and rational use of budgetary funds to meet public sector needs. Before the adoption of the Public Procurement Law of 2014, which aligns closely with EU acquis, public procurement in Bosnia and Herzegovina was regulated at four levels of government, resulting in a highly complex system. One key principle guaranteed by the Public Procurement Law is fair and active competition, which intersects with the Law on Competition in Bosnia and Herzegovina. The Law on Competition regulates the rules, measures, and methods for protecting market competition and outlines the jurisdiction and operations of the Competition Council, which is responsible for promoting and safeguarding market competition. This law further ensures the application of fair and active competition principles. This paper addresses the regulation of bid-rigging in Bosnia and Herzegovina’s public procurement process and investigates whether contracting authorities have encountered bidder behaviors that could indicate bid-rigging, in the context of competition law. To achieve this, the paper is structured into three parts: The first part provides theoretical insights essential for understanding the issue, including international approaches to combating bid-rigging. The second part outlines the regulatory framework for bid-rigging in public procurement within Bosnia and Herzegovina and highlights the significance of public procurement in the country. The third part presents the findings from the research conducted. Based on these findings, the paper offers recommendations for improving the public procurement system in Bosnia and Herzegovina, aiming to eliminate or reduce opportunities for bid-rigging.